Petrogenesis and tectonic implications of the Late Jurassic A-type granite in central Inner Mongolia, North China - Wang, Shuai; Li, Yingjie; Jin, Song; Dong, Peipei; Zhang, Xiawei; Zhao, Dongfang; Kong, Xingrui; Liu, Pengyu (Frontiers in Earth Science, 2023)
Lying along the south of Mongol-Okhotsk Suture Belt (MOSB) in Horqin Right Middle Banner of Inner Mongolia, the Chuhuertu A-type granite is exposed in the Duerji tectonic melange. Based on the systematic field geological characteristics, petrology, geochemistry, zircon U-Pb chronology of it, the purpose of study is to determine the genetic type of pluton, tectonic setting, and provide evidence for the closure time of the ocean basin in study area of Mongol-Okhotsk Ocean (MOO) and the extent of influence in the south of Northeast (NE) China. LA-ICP-MS zircon U-Pb dating shows that the age of the granite is 156.0±2.2Ma, indicating that the formation age is Late Jurassic. The granite is geochemically characterized by high SiO2 (73.04-76.01 wt.%) and alkali (Na2O+K2O=7.81-9.50 wt.%), but low CaO (0.20-0.98 wt.%) and MgO (0.10-0.22 wt.%). The granite has obvious negative Eu anomaly (Eu=0.30-0.75), relative enrichment of Rb, Th, U, K and Ga, depletion of Ba, Sr, P and Ti, as well as high 10000Ga/Al (2.52-2.90), TFeO/MgO (5.76-14.90), (Na2O+K2O)/CaO (7.97-43.45). The petrological, mineralogical and geochemical characteristics of the granite show the characteristics of A-type granite. According to the regional, Mesozoic A-type granites have positive correlation εNd(t) value and young Nd age suggest that the granite may be caused by partial melting of intermediate basic crust in neoaccretion under low pressure and high temperature. Therefore, the influence extent of Mongol-Okhotsk tectonic system in China extends to the southeast at least to the southeastern Inner Mongolia-North Hebei. The zircon U-Pb age of newly obtained Chuhuertu A-type granite restricts the closure time of MOO in study area should be Late Jurassic.